2014
DOI: 10.1039/c4ob00350k
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of lipid-coupled inositol 1,2,3,4,5,6-hexakisphosphate derivatives exhibiting high-affinity binding for the HIV-1 MA domain

Abstract: The precursor of Gag protein (Pr55(Gag)) of human immunodeficiency virus, the principal structural component required for virus assembly, is known to bind d-myo-phosphatidylinositol 4,5-bisphosphate (PIP2). The N-terminus of Pr55(Gag), the MA domain, plays a critical role in the binding of Pr55(Gag) to the plasma membrane. Herein, we designed and synthesized myo-phosphatidylinositol 2,3,4,5,6-pentakisphosphate (PIP5) derivatives comprising highly phosphorylated inositol and variously modified diacylglycerol to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…As Pr55 Gag -PIP2 binding triggers the virion budding, we considered that a small molecule that binds firmly to Pr55 Gag could antagonize PIP2 in the Pr55 Gag binding. Previously, we established a highly-sensitive in vitro assay to determine the dissociation constant ( K d ) for the binding of Pr55 Gag to phosphoinositide derivatives using surface plasmon resonance (SPR) sensor analysis 10 , 11 . We found that both negatively-charged inositol phosphates and the lipophilic acyl chains of phosphoinositide were essential for a strong interaction with Pr55 Gag 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Pr55 Gag -PIP2 binding triggers the virion budding, we considered that a small molecule that binds firmly to Pr55 Gag could antagonize PIP2 in the Pr55 Gag binding. Previously, we established a highly-sensitive in vitro assay to determine the dissociation constant ( K d ) for the binding of Pr55 Gag to phosphoinositide derivatives using surface plasmon resonance (SPR) sensor analysis 10 , 11 . We found that both negatively-charged inositol phosphates and the lipophilic acyl chains of phosphoinositide were essential for a strong interaction with Pr55 Gag 10 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that both negatively-charged inositol phosphates and the lipophilic acyl chains of phosphoinositide were essential for a strong interaction with Pr55 Gag 10 . As well, fully-phosphorylated inositol IP6 (phytic acid, “PA”) bound to the MA domain approximately 10 times stronger than IP3, the inositol head of PIP2 11 . Accounting for each of these details, we had synthesized an artificial phosphoinositide, DL-HIPPO (DL- H eptanoylphosphatidyl I nositol P entakis p h o sphate), as an isomeric mixture (a 1:1 mixture of D-HIPPO and L-HIPPO) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a T-cell line, InsP 6 was also shown to be able to suppress the replication of HIV-1 (Otake et al, 1999). Recently, Tateishi et al (2014) found InsP 6 to be able to tightly bind the matrix domain of the Pr55 Gag protein, which is a critical component for the assembly of the HIV-1 virus. Subsequently, these authors coupled InsP 6 with diacylglycerol moieties to synthesize myo-phosphatidylinositol 2,3,4,5,6-pentakisphosphate derivatives.…”
Section: Inositol Phosphates' Disease Fighting Abilitiesmentioning
confidence: 99%
“…any of currently approved antiretroviral drugs [11][12][13]. Based on the structural information of the MA domain and PI(4,5)P2, we recently developed a non-natural derivative of PI(4,5)P2, named L-HIPPO, which binds to the MA domain in order to eradicate HIV [14,15]. Recent progress identifying cellular interactions of HIV-1 Gag has revealed that the MA domain of the Gag is capable of binding to inositol hexaphosphate (IP6) [14,16] ( Figure 2B & C).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the structural information of the MA domain and PI(4,5)P2, we recently developed a non-natural derivative of PI(4,5)P2, named L-HIPPO, which binds to the MA domain in order to eradicate HIV [14,15]. Recent progress identifying cellular interactions of HIV-1 Gag has revealed that the MA domain of the Gag is capable of binding to inositol hexaphosphate (IP6) [14,16] ( Figure 2B & C). Understanding the dynamic nature of the structural basis of these interactions at high-resolution can provide new hypotheses for HIV therapy.…”
Section: Introductionmentioning
confidence: 99%